Distinguishing Cancerous Liver Cells Using Surface-Enhanced Raman Spectroscopy. (February 2016) - Huang, Jing; Liu, Shupeng; Chen, Zhenyi; Chen, Na; Pang, Fufei; Wang, Tingyun
Raman spectroscopy has been widely used in biomedical research and clinical diagnostics. It possesses great potential for the analysis of biochemical processes in cell studies. In this article, the surface-enhanced Raman spectroscopy (SERS) of normal and cancerous liver cells incubated with SERS active substrates (gold nanoparticle) was measured using confocal Raman microspectroscopy technology. The chemical components of the cells were analyzed through statistical methods for the SERS spectrum. Both the relative intensity ratio and principal component analysis (PCA) were used for distinguishing the normal liver cells (QSG-7701) from the hepatoma cells (SMMC-7721). The relative intensity ratio of the Raman spectra peaks such as I937 /I1209, I1276 /I1308, I1342 /I1375, and I1402 /I1435 was set as the judge boundary, and the sensitivity and the specificity using PCA method were calculated. The results indicated that the surface-enhanced Raman spectrum could provide the chemical information for distinguishing the normal cells from the cancerous liver cells and demonstrated that SERS technology possessed the possible applied potential for the diagnosis of liver cancer.